Levels of assertiveness of LSU Academic and Alumni Scholar - Posadas, Pablita M.; Dagaang, Mary Grace O. (2009)
This study used a descriptive research design which aimed to assess the levels of assertiveness of LSU Academic and Alumni Scholars. It was delved that most of the respondents were highly assertive but are afraid to speak to high ranking officials or officers. It was revealed that some of the respondents could not afford to verbally express their feelings of anger and frustration to concerned people. It was therefore recommended that the respondents be made to realize and understand importance of assertiveness in their lives.
Keywords: Assertiveness (Psychology)